An Insight of Vitamin E as Neuroprotective Agents - Hui-Min Yap; Kwan-Liang Lye (Progress in Microbes and Molecular Biology)
Nervous system is the network of nerve cells that transmits nerve impulses throughout the body. It is rich in both unsaturated fats and irons, making it predominantly susceptible to oxidative stress and damage. Oxidative stress reflects the disruption of the redox balance between the formation and clearance of highly free radicals, for instance reactive oxygen species (ROS) and reactive nitrogen species (RNS). Oxidative stress will further damage the cell lipid, protein and DNA. Oxidative stress has a role in the modulation of critical cellular functions, such as apoptosis program activation, ion transport and calcium mobilization which lead to cell death. Many studies were conducted to prevent neuronal cell death caused by oxidative stress through administration of free radical scavenging antioxidant, such as vitamin E. Vitamin E is known as a chain-breaking antioxidant that showed the capability to increase the viability of neuronal cells that had undergone glutamate injury by inhibiting glutamate-induced pp60 (c-Src) kinase activation. Vitamin E occurs in 8 forms, namely α-, β-, γ- and δ-tocopherols and α-, β-, γ-and δ-tocotrienols. Tocotrienols differ from tocopherols by possessing an unsaturated isoprenoid side chain instead of a saturated phytyl tail. Tocotrienols, compared to tocopherols, are lightly studied due to the abundance of α-tocopherol in the human body and its antioxidant properties. Nevertheless, recent studies showed that α-tocotrienol is more effective in preventing lipid peroxidation compared to α-tocopherol. Furthermore, tocotrienol was discovered to protect neuronal cell through antioxidant-independent activities. The tocotrienol-rich fraction (TRF) is an extract that consists of 75% tocotrienol and 25% α-tocopherol. TRF was reported to possess potent antioxidant, anti-inflammation, anticancer and cholesterol-lowering properties. Thus, this writing highlights the significant neuroprotective effects of tocotrienol and tocopherol.